Micro Germline-Restricted Chromosome in Blue Tits: Evidence for Meiotic Functions - Mueller, Jakob C; Schlebusch, Stephen A; Pei, Yifan; Poignet, Manon; Vontzou, Niki; Ruiz-Ruano, Francisco J; Albrecht, Tomáš; Reifová, Radka; Forstmeier, Wolfgang; Suh, Alexander; Kempenaers, Bart (Molecular biology and evolution, 2023)
The germline-restricted chromosome (GRC) is likely present in all songbird species but differs widely in size and gene content. This extra chromosome has been described as either a microchromosome with only limited basic gene content or a macrochromosome with enriched gene functions related to female gonad and embryo development. Here, we assembled, annotated, and characterized the first micro-GRC in the blue tit (Cyanistes caeruleus) using high-fidelity long-read sequencing data. Although some genes on the blue tit GRC show signals of pseudogenization, others potentially have important functions, either currently or in the past. We highlight the GRC gene paralog BMP15, which is among the highest expressed GRC genes both in blue tits and in zebra finches (Taeniopygia guttata) and is known to play a role in oocyte and follicular maturation in other vertebrates. The GRC genes of the blue tit are further enriched for functions related to the synaptonemal complex. We found a similar functional enrichment when analyzing published data on GRC genes from two nightingale species (Luscinia spp.). We hypothesize that these genes play a role in maintaining standard maternal inheritance or in recombining maternal and paternal GRCs during potential episodes of biparental inheritance.
Keywords: Germ Cells; Chromosomes; birds; genomics; Female; Songbirds; B chromosome; zvířata; germline-restricted chromosome; oocyty; ženské pohlaví; chromozomy; synaptonemal complex; ovarium; zpěvní ptáci; Passeriformes; Animals; Ovary; inheritance pattern; Oocytes; zárodečné buňky